2010
DOI: 10.1186/1746-4269-6-35
|View full text |Cite
|
Sign up to set email alerts
|

Traditional herbal medicine in Far-west Nepal: a pharmacological appraisal

Abstract: BackgroundPlant species have long been used as principal ingredients of traditional medicine in far-west Nepal. The medicinal plants with ethnomedicinal values are currently being screened for their therapeutic potential but their data and information are inadequately compared and analyzed with the Ayurveda and the phytochemical findings.MethodsThe present study evaluated ethnomedicinal plants and their uses following literature review, comparison, field observations, and analysis. Comparison was made against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
140
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(151 citation statements)
references
References 121 publications
9
140
0
2
Order By: Relevance
“…The root of P. fulgens is cut into small pieces and chewed to treat toothache. Manandhar (1995), Subedi (1998), Joshi and Joshi (2000) and Kunwar et al (2010) reported the use of Potentilla fulgens in dental problems similar to the present finding. The flower of Woodfordia fruticosa was also reported to be used in curing dysentery by Manandhar (1990), Manandhar (1992), Acharya (1996), and Oli et al (2005).…”
Section: Intoxicatio Nsupporting
confidence: 78%
“…The root of P. fulgens is cut into small pieces and chewed to treat toothache. Manandhar (1995), Subedi (1998), Joshi and Joshi (2000) and Kunwar et al (2010) reported the use of Potentilla fulgens in dental problems similar to the present finding. The flower of Woodfordia fruticosa was also reported to be used in curing dysentery by Manandhar (1990), Manandhar (1992), Acharya (1996), and Oli et al (2005).…”
Section: Intoxicatio Nsupporting
confidence: 78%
“…However, the use of various plants for fever has been mentioned in the ethnomedicinal studies in Nepal by various workers (Coburn, 1984;Shrestha, 1985;Manandhar, 1985Manandhar, , 1993Manandhar, , 1998Mahato, 1998;Dangol and Gurung, 2000;Devkota and Karmacharya, 2003;Shrestha and Dhillion, 2003;Oli, 2003;Rai, 2003;Panthi and Chaudhary, 2003;Rai, 2004;Acharya and Rokaya, 2005;Watanabe et al, 2005;Acharya and Pokhrel, 2006;Baral and Kurmi, 2006;Bhattarai et al, 2006Bhattarai et al, , 2009Burlakoti and Kunwar, 2008;Dangol, 2008;Joshi, 2008;Dhami, 2008;Sapkota, 2008;Acharya and Acharya, 2009;Ghimire and Bastakoti, 2009;Joshi and Singh, 2010;Kunwar et al, 2010;Rokaya et al, 2010;Uprety et al, 2010;Joshi et al, 2011;Singh et al, 2011 a, b, c and2012;). Pharsatikar, P. Amuwa, and Devdaha) in Rupandehi district.…”
Section: Introductionmentioning
confidence: 99%
“…It is also used to treat skin disease, snake bite, and jaundice. 15,16 In the present study, we investigated the antibacterial activity of various organic extracts of A. indica against several human pathogenic bacteria. To this end, the chemical composition of the essential oil from A. indica was investigated by gas chromatography-mass spectrometry (GC-MS), with an emphasis on the possible future use of extracts of this plant as alternatives to chemically synthesized antibiotics and/or as substances for generic drug design.…”
Section: Introductionmentioning
confidence: 99%